SRF2—A Short‐Term (1–24)h foF2 Prediction Method - L. Perrone; A. V. Mikhailov (Space Weather)
Abstract A sunrise F2‐layer short‐term (1–24) h foF2 prediction method has been developed to forecast foF2 variations at a given ionosonde station during magnetically quiet and disturbed periods. The proposed method efficiently describes both positive and negative quiet time F2‐layer disturbances under daily Ap <30 nT and this was done for the first time. A comparison with modern global empirical models demonstrates a statistically significant advantage over them under various seasons and levels of solar activity.